Analisis Kebijakan Redaksional Harian Republika pada Pemberitaan Religio-Politik Masa Kampanye Presiden Tahun 2009 - Fanani, Fajriannoor (Jurnal The Messenger, 2011)
Presidential Election in 2009 has gives us some negative phenomenon. The Hijab Campaign, Boediono Wife s Religion, and other religio-politics issues were annoyingly interpolating the better campaigns. In one hand this is a bad phenomenon, but on the other hand this phenomenon also gives us some interesting questions about political tolerance in Indonesia. Mass media as the fourth estate surely can t get away from their responsibility. Uniquely many of big mass media in Indonesia have affiliations with certain religions. The example is Republika with their Muslim affiliations. This phenomenon become interesting to study, moreover Indonesia is one of the biggest democratic countries in the world that surely need political tolerance to strengthen their democratic system. It s become interesting to inquire the editorial policy in Republika in their news on religio-politic in presidential campaign. It s also become interesting to understand the Islamic model that Republika adopted that maybe affected their editorial policy. Last, it s become interesting to find out Republika s political tolerance, especially in the presidential campaign. All of this inquiry could be found using the gatekeeping analysis from Pamela Shoemaker that map out factors that could affect media content from five levels. Those levels are individual, organizational, communication routine, extra-media, and social system.This research is use post-positivistic paradigm. The theories used here is gatekeeping from Pamela Shoemaker, political tolerance, and moderate Islamic concepts. After analyze using the gatekeeping Analysis, this research found that Republika s policy for the religio-politics issues have vision of moderat Islamic model that generally careful but will be serious and sensasional if when dealing with syariah policy issues. Last, Republika have a limited political tolerance policy that have tendency to be exclusive and difficult to accommodate the aspiration of non-Muslim peoples.   The final conclusion for this research is that Republika have an editorial policy that creates public space for Indonesian Muslim that has vision of Islamic moderate and limited political tolerance.